2021
DOI: 10.2337/db21-0659
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Control Effector T Cell Inflammation in Human Prediabetes

Abstract: A disparate array of plasma/serum markers provide evidence for chronic inflammation in human prediabetes, a condition that is most closely replicated by standard mouse models of obesity and meta-flammation. These remain largely non-actionable, and contrast with our rich understanding of inflammation in human type 2 diabetes. New data show that inflammatory profiles produced by CD4+ T cells define human prediabetes as a unique inflammatory state. Regulatory T cells (Tregs) control mitochondrial function and cyt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…To determine the relative contributions of myeloid and T cells to Figure 1G). We conclude, from both CD3/CD28-and LPS-elicited profiles, that metabolic status impacts cytokine competency in cells from donors with obesity, consistent with our work on purified CD4 + T cells [30].…”
Section: Pbmcs Increase Cytokine Production With Time Following T Cel...supporting
confidence: 88%
See 1 more Smart Citation
“…To determine the relative contributions of myeloid and T cells to Figure 1G). We conclude, from both CD3/CD28-and LPS-elicited profiles, that metabolic status impacts cytokine competency in cells from donors with obesity, consistent with our work on purified CD4 + T cells [30].…”
Section: Pbmcs Increase Cytokine Production With Time Following T Cel...supporting
confidence: 88%
“…Responses to T cell-targeted CD3/CD28 underscored the distinctiveness of preT2D inflammation first indicated by our analysis of cytokine competency of purified CD4 + T cells [30] and significantly extends existing analyses of cytokines in preT2D plasma/serum [39,40]. The acute myeloid response, combined with the more sustained response to CD3/CD28 that dominates overall "inflammation" at 72 hours, is consistent with a canonical immune response in which innate immune cells respond quickly to prime a sustained adaptive immune response.…”
Section: T Cell Cytokine Competency Disproportionately Contributes To...supporting
confidence: 54%
“…The authors stimulated cells with CD3/CD28 beads for 40 hr and then quantified secreted cytokines in a 25-cytokine multiplex ( Ip et al, 2016 ; Beste et al, 2014 ; Lau et al, 2012 ). IL-10 was produced in greater amounts from cells of lean/healthy donors, and there were differences in production of Th1/Th17 cytokines, that is, more CCL-20, TNFα, GM-CSF in prediabetes, and less IL-6/-12 were noted ( Liu et al, 2022 ). These data are consistent with the tenet that metabolic status, independent of age, significantly shifts inflammatory profiles.…”
Section: Metabolic Dysfunction and Acute Sars-cov-2mentioning
confidence: 99%
“…CD4 + T cells influence obesity-associated inflammation, especially the systemic inflammation that provokes numerous obesity comorbidities in people. A recent study showed that CD4 + T cells from subjects with prediabetes produces a unique inflammatory profile [48]. A better understanding of CD4 + T change in prediabetes is also important for clarifying the gut microbiota-host immunity interaction in metabolic disease.…”
Section: Discussionmentioning
confidence: 99%